2004
DOI: 10.1104/pp.104.043398
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Auxin Conjugate Hydrolase from Wheat with Substrate Specificity for Longer Side-Chain Auxin Amide Conjugates

Abstract: This study investigates how the ILR1-like indole acetic acid (IAA) amidohydrolase family of genes has functionally evolved in the monocotyledonous species wheat (Triticum aestivum). An ortholog for the Arabidopsis IAR3 auxin amidohydrolase gene has been isolated from wheat (TaIAR3). The TaIAR3 protein hydrolyzes negligible levels of IAA-Ala and no other IAA amino acid conjugates tested, unlike its ortholog IAR3. Instead, TaIAR3 has low specificity for the ester conjugates IAA-Glc and IAAmyoinositol and high sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 78 publications
1
46
0
Order By: Relevance
“…Temporal expression studies of TaIAR3 indicate that the transcript is initially expressed at day 1 after germination and then expression decreases through days 2, 5, 10, 15, and 20. Spatial expression studies found similar levels of expression throughout all wheat tissues examined (Campanella et al, 2004). Our study results showed that the transcription level of TaIAR3 in branched spike line increased much higher than those in normal spike lines in young shoot and young leaves after the two ridges stage.…”
Section: Discussionsupporting
confidence: 54%
“…Temporal expression studies of TaIAR3 indicate that the transcript is initially expressed at day 1 after germination and then expression decreases through days 2, 5, 10, 15, and 20. Spatial expression studies found similar levels of expression throughout all wheat tissues examined (Campanella et al, 2004). Our study results showed that the transcription level of TaIAR3 in branched spike line increased much higher than those in normal spike lines in young shoot and young leaves after the two ridges stage.…”
Section: Discussionsupporting
confidence: 54%
“…These changes were associated with high mRNA levels of genes encoding enzymes of amino acid biosynthesis, implying that amino acid biosynthesis apparently continues during the desiccation period, and that at least some amino acids significantly accumulate in their free forms rather then being incorporated into storage proteins. These lines of evidences taken in the context of current models of seed metabolism suggest that the seed desiccation process preferentially favors (1) the decrease of the C/N ratio, (2) the accumulation of free amino acids rather than storage proteins, and (3) the production of shikimate-derived secondary metabolites associated with defense (Hull et al, 2000;Glawischnig et al, 2004;Piotrowski et al, 2004) and indole-3-acetic acid biosynthesis (Campanella et al, 2004;Sharaf and Farrag, 2004) that are necessary triggers for seed germination (Normanly, 1997;Slavov et al, 2004). In addition to the accumulation of free amino acids and various carbon metabolites, the period of seed desiccation was also associated with small increases in the levels of various fatty acids, fatty acid-related compounds such as glycerol, as well as intermediates of fatty acid degradation (Fig.…”
Section: The Transition From Reserve Accumulation To Seed Desiccationmentioning
confidence: 99%
“…Besides IBA synthetase activities in maize and Arabidopsis, IBA glucosylation activity in Arabidopsis Ludwig-Mü ller, 2007) and IBA-Ala hydrolase in wheat (Triticum aestivum) (Campanella et al, 2004), the identity of the plant genes involved in IBA biosynthesis, conjugation, and/or hydrolysis remained unknown . Here, we demonstrate that UGT74E2 is an IBA glucosyltransferase with a high and preferred activity toward IBA in in vitro assays and that its overexpression resulted in increased IBA-Glc levels in planta (Figure 2, Table 1).…”
Section: Ugt74e2 Perturbs Auxin Homeostasismentioning
confidence: 99%